Subchronic N-acetylcysteine Treatment Decreases Brain Kynurenic Acid Levels and Improves Cognitive Performance in Mice - Tonali Blanco Ayala; Daniela Ramírez Ortega; Paulina Ovalle Rodríguez; Benjamín Pineda; Gonzalo Pérez de la Cruz; Dinora González Esquivel; Robert Schwarcz; Korrapati V. Sathyasaikumar; Anabel Jiménez Anguiano; Verónica Pérez de la Cruz (MDPI AG, 2021)
The tryptophan (Trp) metabolite kynurenic acid (KYNA) is an α7-nicotinic and N-methyl-d-aspartate receptor antagonist. Elevated brain KYNA levels are commonly seen in psychiatric disorders and neurodegenerative diseases and may be related to cognitive impairments. Recently, we showed that N-acetylcysteine (NAC) inhibits kynurenine aminotransferase II (KAT II), KYNA's key biosynthetic enzyme, and reduces KYNA neosynthesis in rats in vivo. In this study, we examined if repeated systemic administration of NAC influences brain KYNA and cognitive performance in mice. Animals received NAC (100 mg/kg, i.p.) daily for 7 days. Redox markers, KYNA levels, and KAT II activity were determined in the brain. We also assessed the effect of repeated NAC treatment on Trp catabolism using brain tissue slices ex vivo. Finally, learning and memory was evaluated with and without an acute challenge with KYNA's bioprecursor L-kynurenine (Kyn; 100 mg/kg). Subchronic NAC administration protected against an acute pro-oxidant challenge, decreased KYNA levels, and lowered KAT II activity and improved memory both under basal conditions and after acute Kyn treatment. In tissue slices from these mice, KYNA neosynthesis from Trp or Kyn was reduced. Together, our data indicate that prolonged treatment with NAC may enhance memory at least in part by reducing brain KYNA levels.